Bioethanol Generation Through the Fermentation Process of Pineapple and Black Grape Utilizing Saccharomyces cerevisiae and Saccharomyces bayanus - Ika Nawang Puspitawati; Sintha Soraya Santi; Kindriari Nurma Wahyusi; Sani (Nusantara Science and Technology Proceedings, 2023)
Bioethanol is an alcohol molecule that is derived through the process of fermentation using microorganisms. Fermentation is a biological process in which microbes metabolize fermentable sugars as a source of nourishment, resulting in the production of ethyl alcohol and various other byproducts. These microbes commonly metabolize 6-carbon carbohydrates, with glucose being one of the most prevalent examples. Hence, biomass materials rich in glucose or glucose precursors are the most readily convertible to bioethanol. The examination of bioethanols employing Saccharomyces bayanus demonstrated notable disparities in the obtained alcohol concentration. The utilization of Saccharomyces bayanus yeast, in the absence of sugar supplementation, for the conversion of grape into bioethanol, yielded a modest alcohol concentration of merely 14%. In the context of bioethanol production, pineapple was utilized as a substrate, wherein 4 grams of Saccharomyces bayanus yeast and an additional 70 grams of sugar were introduced as a nutritional supply to support yeast growth and metabolism. The present fermentation procedure resulted in an alcohol concentration of around 21%.